2022
DOI: 10.1007/s10681-022-03141-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the inheritance pattern of the anemone flower type and tubular floral traits of chrysanthemum in segregating F1 populations

Abstract: Anemone type, featuring prominent and colored in tubular orets, is an attractive ower shape in chrysanthemums and thus desired by breeders and consumers. Understanding the genetic basis of anemone-type owers in chrysanthemum is crucial for breeding success. The current study conducted nine cross combinations from seven parents to investigate segregation patterns, parental effect, and the relationships between the heterosis of six tubular oral traits and parental genetic distance. The results showed signi cant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…These findings suggest that a substantial proportion of the variance is explained by genetic factors in traits with heritability values above 0.50. Similar values have been reported for crosses and hybrid populations of various species, such as Chrysanthemum morifolium Ramat., Argentina anserine (L.) Rydb., Iris × hybrida Hort., and Crocus sativus L. In these studies, broad‐sense heritability ranging from 0.34 to 0.92 accounted for different floral traits associated with flower size and shape (Baghalian et al., 2010; Fan et al., 2019; Koski & Ashman, 2013; Yang et al., 2023). Our results of broad‐sense heritability remained consistently stable across the three evaluated populations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that a substantial proportion of the variance is explained by genetic factors in traits with heritability values above 0.50. Similar values have been reported for crosses and hybrid populations of various species, such as Chrysanthemum morifolium Ramat., Argentina anserine (L.) Rydb., Iris × hybrida Hort., and Crocus sativus L. In these studies, broad‐sense heritability ranging from 0.34 to 0.92 accounted for different floral traits associated with flower size and shape (Baghalian et al., 2010; Fan et al., 2019; Koski & Ashman, 2013; Yang et al., 2023). Our results of broad‐sense heritability remained consistently stable across the three evaluated populations.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting the evolution of floral morphology toward larger flowers is more favorable for pollinators [ 45 ]. Understanding the genetic control model of flower traits is of great significance for breed improvement in plants [ 46 ]. Previous studies found that, in peaches, the phenotype of multi-petal flowers is a single recessive trait [ 47 ], while the single-petal flower type is controlled by a recessive allele in carnations [ 48 ].…”
Section: Discussionmentioning
confidence: 99%